Community-Metabolome Correlations of Gut Microbiota from Child-Turcotte-Pugh of A and B Patients - Wei, Xiao; Jiang, Shan; Zhao, Xiangna; Li, Huan; Lin, Weishi; Li, Boxing; Lu, Jing; Sun, Yansong; Yuan, Jing (Frontiers in Microbiology, 2016)
The gut flora are widely involved in the cometabolism with the host and have evident effects on the metabolic phenotype of host. This study performed a metabolome analysis of the intestinal microbiota specific for liver cirrhosis. The study population included patients with Child-Turcotte-Pugh (CTP) score of A (AP, n=5) and B (BP, n=5), and control subjects (NM, n=3). Metagenomic DNA from fecal microbiota was extracted followed by metagenomic sequenceing through Illumina MiSeq high throughput sequencing of 16S rRNA regions. The detection of metabolites from fecal samples was performed using high-performance liquid phase chromatography and gas chromatography coupled with tandem mass spectrometry (HPLC-GC/MS-MS). Intestinal microbiota community and metabolite analysis both showed separation of cirrhotic patients from control participants, moreover, the microbiota-metabolite correlations changed in cirrhotic patients. Fecal microbiota from cirrhotic patients, with the reduced diversity, contained a decreased abundance of Bacteroidetes and an increased abundance of Proteobacteria compared with the normal samples. Analysis of metabolome revealed a remarkable change in the metabolic potential of the microbiota in cirrhotic patients, with specific higher concentrations of amine, unsaturated fatty acid, and SCFAs (short-chain fatty acids), and lower concentrations of sugar alcohol and amino acid, suggesting the initial equilibrium of gut microbiota community and co-metabolism with the host were perturbed by cirrhosis. Our study illustrated the relationship between fecal microbiota composition and metabolom in cirrhotic patients, which may improve the clinical prognosis of cirrhosis.